A nomogram based on LI-RADS features, clinical indicators and quantitative contrast-enhanced MRI parameters for predicting glypican-3 expression in hepatocellular carcinoma - Song, Yan; Zhang, Yue-yue; Yu, Qin; Chen, Tong; Wei, Chao-gang; Zhang, Rui; Hu, Wei; Qian, Xu-jun; Zhu, Zhi; Zhang, Xue-wu; Shen, Jun-kang (Frontiers in Oncology, 2023)
Purpose: Noninvasively assessing the tumor biology and microenvironment before treatment is greatly important, and glypican-3 (GPC-3) is a new-generation immunotherapy target for hepatocellular carcinoma (HCC). This study investigated the application value of a nomogram based on LI-RADS features, quantitative contrast-enhanced MRI parameters and clinical indicators in the noninvasive preoperative prediction of GPC-3 expression in HCC. Methods and materials: We retrospectively reviewed 127 patients with pathologically confirmed solitary HCC at the Second Affiliated Hospital of Soochow University from January 2018 to January 2022 who underwent Gd-EOB-DTPA MRI examinations and related laboratory tests. Quantitative contrast-enhanced MRI parameters and clinical indicators were collected and recorded by intermediate- and senior-level abdominal radiologists, and LI-RADS features were independently assessed and recorded by three trained intermediate- and senior-level radiologists. The pathological and immunohistochemical results of HCC were determined by two senior pathologists. Finally, 127 patients were divided into a GPC-3-positive (82 cases) and GPC-3-negative group (45 cases). Univariate analysis and multivariate logistic regression were performed to identify independent predictors of GPC-3 expression in HCC, and a nomogram model was established. Results: The following parameters significantly differed between groups: LI-RADS features: tumor size, blood products in mass, restricted diffusion, nodule-in-nodule architecture, mosaic architecture, and enhanced capsule; quantitative parameters of MRI enhancement: contrast enhancement ratio (CER), transition phase lesion-liver parenchyma signal ratio (TP-LNR), and hepatobiliary phase lesion-liver parenchyma signal ratio (HBP-LNR); and clinical indicators: serum ferritin (Fer). In multivariate logistic regression, blood products in mass, nodule-in-nodule architecture, mosaic architecture, CER, TP-LNR, and Fer were independent predictors of GPC-3 expression, with odds ratios (ORs) of 3.871, 4.829, 3.015, 4.716, 0.013, and 1.003, respectively. Nomogram based on LI-RADS features, quantitative contrast-enhanced MRI parameters and clinical indicators for predicting GPC-3 expression in HCC was established successfully. The Area under the receiver operating characteristic curve of the nomogram was 0.891, and the calibration curve and decision curve analysis (DCA) had good consistency and clinical utility. Conclusion: The nomogram constructed from LI-RADS features, quantitative contrast-enhanced MRI parameters and clinical indicators has high application value, can accurately predict GPC-3 expression in HCC and may help noninvasively identify potential patients for GPC-3 immunotherapy.